Strategic Management Accounting in Organizations’ Cash Flow Control - Vetrov, Y. P.; Vandina, O. G.; Galustov, A. R. (Journal of History Culture and Art Research, 2017)
The article deals with the various interpretations of the term "strategic management accounting". The role and importance of strategic management accounting in the organization’s cash flows control are investigated. The accounting and analytical models of strategic management accounting are analyzed. The territorial scope of this article covers the Russian Federation. The study concludes that the system of assessment parameters of organization’s financial condition should cover all its aspects, namely, financial sustainability, solvency, liquidity and business activity. Hence, strategic management accounting of cash flows makes it possible to correctly set information base to monitor financial flows of a company which responds the tends of market economy and allows to make optimal management decisions.